The activity-based cost - Pacheco Mexzon, Raimundo Renaun (2014)
When a company produces for the market more than one product should allocate Indirect Costs Manufacturing (ICM) in the best possible way to these products. The activity-based cost system, also called ABC system allows each product ICM more realistically apply. Therefore it is an object of this article how to apply this system and compare the result with the traditional method.